Legal Categorization and Implications of the Placement of the Notary Profession in the Indonesian Standard Business Classification - Anugrah Haryata Pratama (Authentica, 2023)
Article 1 point 1 of Law Number 30 of 2004 concerning the Office of a Notary Public explains that a Notary is a public official authorized to make authentic deeds in accordance with the Law on the Position of a Notary Public and other laws. From the other side, the regulation of the Head of the Central Bureau of Statistics Number 2 of 2020 concerning the Indonesian Standard Business Classification whose purpose is to classify economic activities in Indonesia states that Notaries are categorized together with other business actors in code 69104. Mention of Notaries in Indonesian Standard Business Classification's efforts to make Notaries able to move into entrepreneurs in accordance with the title of classification number 69104" Activities of Notaries and Land Deed Officials " whose categorization is the same as other business actors so that makes the author interested in researching this matter. Based on the case above, there are two formulations of the problem, namely: How is the placement of implications arising from the position of a Notary Public categorized as self-employed according to the Regulation of the Head of the Central Bureau of Statistics Number 2 of 2020 concerning the Indonesian Standard Business Classification; How is the harmonization between Law Number 30 of 2004 concerning the Position of Notary Public and the Regulation of the Head of the Central Statistics Agency Number 2 of 2020 concerning the Indonesian Standard Business Classification. The research method that the author uses is normative juridical by studying the law and then clashing between laws and regulations.Keywords: Notary, Enterpreneur, Categorization, Legal Implications, Placement of Notary Profession, Indonesian Standard Business Classification